Development of PID auto-tuner for TITO systems - Wang, Tie Han. (2008)
This dissertation presents the research of development of a TITO Auto-tuner. The theoretical research and application of PID auto-tuning are extended to TITO control system, a complex PID control system. A novel auto-tuning technique for TITO control systems is proposed. In this work, frequency domain test is carried out to identify all process models simultaneously by utilizing the physical properties of TITO control systems. The advantage of the novel method is that it replaces conventionally cumbersome and time-consuming auto-tuning procedures for the TITO control systems. It saves the tuning time and is more effective.